Enhancing learning through human computer interaction - McKay, Elspeth (Gale virtual reference library)
A manual for the novice-Human Computer Interaction (HCI) designer. Compares and contrasts online business training programs with e-Learning in the higher education sector and provides a range of positive outcomes for linking information management techniques, which exploit the educational benefits of Web-mediated learning in computer supported collaborative learning.